Comparison of methods used for elimination of matrix effect in ICP-AES - Krejčová, Anna; Černohorský, Tomáš (Univerzita Pardubice, 2004)
The determination of Al, Be, Cd, Co, Cr, Cu, Mn, Ni, Pb, V and Zn in high-saline solutions (urine) by ICP-AES method has been studied. The interference due to individual components (NaCl, KCl, CaCO3, MgCl2, NH4H2PO4, HCl, H2SO4 and urea) and their concentration levels were evaluated. Suppression of down to 20% of trace element content was found due to the main inorganic components of urine. The methods for correction of matrix effect, i.e. internal standardisation with Y, Sc and Ar and the "CAIS" technique were tested and and compared with the results of direct determination. The organic components of urine had no significant effect. Two approaches of estimation of LOD were used. The influence of urine matrix on LOD was established. Precision (RSD) was about 1% for internal standardisation and less than 2% for direct estimation. The accuracy was evaluated with urine control materials Seronom Trace Element Urine, batch 403125 (Nycomed Pharma), and Lyhpochek 69012 (Bio-Rad).